The Paradigm of Creative Class in a Global Milieu - Iryna Skavronska (Universal Journal of History and Culture)
This paper discusses the creative class as a new layer of contemporary society that drives entrepreneurship, innovation and dynamism of economy. Current social and economic transformations are caused by new factors which affect the emergence of creative class. The potential of creative professionals has become one of the major means of the national development as it contributes to maximizing welfare, enriches consumption and improves standards of living. Creative class is a strategic input for companies and government agencies looking for more effective communication and new ways to stand out. The purpose of this study is aimed at the in-depth clarifying and summarizing of the theoretical background about creative class in a global milieu, including its specific lifestyle, and how it relates to other concept such as creative employment. The underlying argument is that creativity is one of the constructs of those skills, knowledge and abilities required by the modern labor market in the face of globalization challenges. The presented findings of the paper include a more holistic approach to identifying a range of determinants and metrics important for the successful promotion of creative employment. In light of these findings, the article concludes with discussing the rise of creative class in a global scale.